(untitled) (Journal of Science and Technology, 2016)
To evaluate the usefulness of two Salix species in pastoral systems, two experiments were conducted to determine 1) the effects of browsing intensity and frequency on the regrowth of the Salix species and Chamaecytisus palmensis (H. Christ) Hutch and 2) sheep preference for them. The species responded well to browsing but the mean regrowth of S. kinuyanagi Kimura and C. palmensis was higher than that for S. matsudana x alba clone ‘Tangoio’. Across species, browsing twice during summer-autumn yielded more edible dry matter (DM) than browsing once and seemed the most practical management for the farmer. Heavy browsing increased woody stem DM in S. kinuyanagi but did not influence regrowth in S. matsudana x alba and C. palmensis. S. matsudana x alba was the most preferred species by sheep but declined dramatically in preference during autumn. It is suggested that C. palmensis must be grown alone to enhance its use while the Salix spp. could be mixed.